AB0290 Certolizumab Pegol Exposure in Rheumatoid Arthritis Pregnancies: A Case Series. (9th June 2015) - Meroni, M.; Pizzorni, C.; Paolino, S.; Gerbaldo, D.; Gustavino, C.; Seriolo, B.; Cutolo, M.
Abstract : Background: TNF alpha (TNFα) has a dual role during pregnancy course: in its first phase, promotes embryo implantation and endometrial vascular differentiation via cyclo-oxygenase and subsequent prostaglandins production; at the end of the third trimester, it contributes to the labor onset by regulating uterine contractions [1]. TNFα increased levels, although, have been associated to pregnancy complications. Among anti-TNFα agents indicated for RA treatment is included certolizumab pegol (CTZ). A double peak of incidence of RA in the female gender is linked to the hormonal status changes: the majority of women becomes ill during the post-menopausal age, but a percentage around 10% experiences the disease during the reproductive age [2]. Even if pregnancy has always been considered having a positive impact on RA symptoms [3], disease flares are occasionally observed, raising the challenge of RA management before/in the early stages of pregnancy. Objectives: To assess the CTZ use safety during RA pregnancies. Methods: In cooperation with the Obstetrics and Gynecology Division, we retrospectively considered, since 2010, 7 RA patients, diagnosed according to the 2010 ACR/EULAR criteria and exposed to CTZ just at the beginning (1st trimester) or during the whole pregnancy. Local ethic committee previously approved this rescue treatment and all patients signed an informed consent regarding the potential risk of biologic agents on fetus. Results: The totality of patients was free from taking any potentially teratogenic drug like methotrexate or leflunomide, that were been stopped in the view of pregnancy. In 5/7 patients, thanks to an improvement of RA symptoms and laboratory tests, CTZ treatment was stopped during the first trimester of pregnancy. In 2 cases, on the opposite, the high disease activity required a prosecution of biologic administration until the end of the second trimester. All patients were treated by low-dose of oral prednisone (average 5±2.5 mg daily); two subjects were on sulfasalazine administration (both on 500 mg three times daily) and two others on hydroxychloroquine (200 mg, twice daily). Mean maternal age at conception was 31.6±3.4 years; mean disease duration dated of 51±26 months. Mean gestation period was 39±0.8 weeks and mean birth weight 3.037±0.58 grams. Three patients deliveries required cesarean section, while the others experienced a normal vaginal delivery (2 labor were induced by intravenous oxytocin). Mean APGAR scores after 1, 5 and 10 minutes from delivery were, respectively, 8±2; 8±1 and 9±1. No obstetric, perinatal or neonatal complications were observed. No relevant side effects were detected in relation to the CTZ treatment. However, none of the newborn was breastfed, due to the lack of data about CTZ safety. Conclusions: Our data seem to suggest an overall safety of CTZ administration even during pregnancy in RA patients requiring intensive treatment. Further large data collection perspective, controlled studies are absolutely needed to confirm this pilot survey. References: Marchioni RM. World JJ Gastroenterol 2013;19:2591-602. Cutolo M, et al. Expert Rev Clin Immunol 2014;10:31-9. Østensen M, et al. Autoimmun Rev 2012;11:A437-46. Disclosure of Interest: None declared